1998
DOI: 10.1021/jo981628j
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Reactivity of Penicillins and Cephalosporins. Intramolecular Involvement of the Acyl-Amido Side Chain

Abstract: The rate of degradation of 6-epi-ampicillin in acidic, neutral, and alkaline aqueous solutions was followed at 35°C and an ionic strength of 0.5 mol dm -3 (KCl) by high-performance liquid chromatography (HPLC) and spectrophotometric assays. Pseudo-first-order rate constants were determined in a variety of buffer solutions, and the overall pH-rate profile was obtained by extrapolation to zero buffer concentration. The hydrolysis of 6-epi-ampicillin is subject to acid and hydroxide-ion catalysis and, for a penic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 41 publications
1
18
0
Order By: Relevance
“…In good agreement with previous reports, 34 we determined that the uncatalyzed first-order rate for benzyl penicillin (BP) hydrolysis in buffer A (100 mM sodium phosphate, (pH 7.0 at 25 8C)) is 2.6!10 K7 s K1 . Also, we found that the rate in the presence of lysozyme or bovine serum albumin (BSA) is similar to that in buffer alone (Table 2).…”
Section: Catalysis As a Probe For Native Foldingsupporting
confidence: 91%
“…In good agreement with previous reports, 34 we determined that the uncatalyzed first-order rate for benzyl penicillin (BP) hydrolysis in buffer A (100 mM sodium phosphate, (pH 7.0 at 25 8C)) is 2.6!10 K7 s K1 . Also, we found that the rate in the presence of lysozyme or bovine serum albumin (BSA) is similar to that in buffer alone (Table 2).…”
Section: Catalysis As a Probe For Native Foldingsupporting
confidence: 91%
“…1. AX was obtained from Glaxo Smithkline Beecham (Madrid, Spain), amoxicilloic acid was prepared following the same approach as for benzylpenicilloic acid (7), and diketopiperazine was prepared according to Llins (12).…”
Section: Methodsmentioning
confidence: 99%
“…All involve the transfer of acyl groups via a covalent bond between the carbon atom in the carbonyl group and the attacking nucleophile to form a tetrahedral intermediate T that subsequently undergoes cleavage of the C N bond in the ␤-lactam ring (see Scheme 1). In these processes, the nucleophilic attack can take place on both the ␣ and ␤ sides of the antibiotic; in penicillins, however, the approach on the ␤ side is sterically hindered by the C 3 -␤-proton and the 2-␤-methyl group, so the attack occurs preferentially on the ␣ side [20].…”
Section: Introductionmentioning
confidence: 99%